MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN TUNTUNAN SUARA BACAAN WUDHU DAN TAJWID UNTUK ANAK SEKOLAH DASAR - Muhammad Fahrurrozi; Lalu Puji Indra Kharisma; Yoviana Yoviana (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Islamic Religious Education (PAI) learning in elementary schools faces several major challenges, one of which is low student interest in this learning, mainly due to teaching methods that tend to be monotonous and less interactive. The limited variety of learning resources and interesting are several important factors in the lack of interest in PAI, many students find it difficult to understand PAI material because the delivery is not relevant to the current digital learning style. The availability of interactive learning media relevant to current digital learning is certainly very necessary. Interactive Learning Media Using Voice Guidance for Wudhu and Tajwid Readings for Elementary School Children is a solution that can be used as a learning tool to increase children's interest in learning independently anytime and anywhere. This learning media is an Android-based application that can be run on smartphones. Interactive elements such as visuals, videos, and audio in the application are expected to increase student engagement in the learning process better. Theoretically, this research can add to the development of Android-based learning media in the field of PAI, especially for practical materials. Practically, this application can be a useful resource for teachers, students, and the community in understanding and practicing Wudhu and tajwid procedures. This research is expected to significantly improve the quality of Islamic Religious Education (PAI) learning. The results of the trial implementation of the learning media at SDN 2 Rarang, East Lombok Regency, West Nusa Tenggara, showed a 100% positive. Based on the feedback and reactions given by teachers and students, it shows that the application created runs well and helps teachers and students in achieving learning targets.Keywords: Interactive Learning Media, Wudhu, Tajwid